Pengaruh Sistem Informasi Akuntansi Penerimaan Kas Terhadap Pengendalian Intern Penerimaan Kas : (Studi pada salah satu perusahaan penginapan di Kabupaten Bandung Barat) - Galih Muhamad; Djajun Juhara; Annita Jannah; Adam Ramdhani (Acman: Accounting and Management Journal, 2021)
The role of accounting information systems and internal control in an organization is critical in presenting information related to business decisions. Therefore, the effectiveness of the accounting information system and internal control must facilitate the decision-making process by the management. This research departs from the problems that occur in the internal control of cash receipts which are thought to be caused by the ineffectiveness of the cash receipts accounting information system. This study aims to determine the effect of the cash receipts accounting information system on the internal control of cash receipts. The research method used is a survey method on 30 employees of a lodging service company. A simple regression analysis technique was used to answer the problem formulation. The results showed a significant effect of cash receipts accounting information systems on internal control of cash receipts. The study results recommend that the company further improve the accounting information system of cash receipts and internal control of cash receipts to achieve organizational goals.